Peningkatan Rasio Kompresi Algoritma RLE Menggunakan Transormasi bwt - Syahputra, Rian (Jurnal Sains dan Teknologi (JSIT), 2021)
In file compression, especially image files, it is expected that the results obtained using a compression method will be smaller than before, because usually storage for image files uses a lot of memory capacity. To get better results, a combination of compression methods is used, namely BWT with RLE. To produce a better compression ratio, 2 scenarios are used, the first using the results from the second and third stages of the BWT algorithm. From the RLE algorithm, it was found that the size increased by 10%, with the results of the second stage of the BWT algorithm, the size ratio decreased by 58.33% and with the results of the third stage of the BWT algorithm, the size ratio increased by 44.44%.